The Individual and Joint Performance of Economic Preferences, Personality, and Self-Control in Predicting Criminal Behavior - Tim Friehe; Hannah Schildberg-Hörisch (Center for Economic Studies and ifo Institute (CESifo), 2014)
We explore the individual and joint explanatory power of concepts from economics, psychology, and criminology for criminal behavior. More precisely, we consider risk and time preferences, personality traits from psychology (Big Five and locus of control), and a self-control scale from criminology. We find that economic preferences, personality traits, and self-control complement each other in predicting criminal behavior. The most significant predictors stem from all three disciplines: risk aversion, conscientiousness, and high self-control make criminal behavior less likely. Our results illustrate that integrating concepts from various disciplines enhances our understanding of individual behavior.
Keywords: D03; K42; 330; crime; risk preferences; time preferences; personality traits; self-control; experiment